Splenectomy in cases of splenic Hemangiosarcoma - Andrade, Vanessa Gonçalves de; Carvalho, Ana Maria Guimarães; Fernandes, Bianca Jacqueline Silva; Borges, Igor Leonardo Resplandes; Espíndola, Ivan Ricardo Matos; Oliveira, Ívina Myrelle Santana; Sousa, Karoline Pereira de; Silva, Thiago Viríssimo Rocha; Silva, Vitória Fernanda Ferreira da; Santos, Vyrginia Stheffany Fernandes dos (Seven Editora, 2023)
Hemangiosarcoma is a neoplasm of the vascular endothelium, extremely aggressive and highly metastatic, which can affect several organs. However, the spleen is one of the most commonly found in dogs that have this type of alteration. The spleen is an organ that has several important functions for the homeostatic functioning of the animal organism, however, in the treatment of this neoplasm, the recommendation is that a total splenectomy be performed together with antineoplastic chemotherapy. In order to carry out this procedure, it is important that the entire clinical status of the animal be analyzed in advance, in addition to carrying out laboratory and imaging tests, with computed tomography being indicated for surgical planning. Despite being a technique that removes an organ, the animal can still live well without it, and the surgical procedure may prolong the lives of those with splenic hemangiosarcoma. DOI:https://doi.org/10.56238/alookdevelopv1-066